2014
DOI: 10.21101/cejph.a3900
|View full text |Cite
|
Sign up to set email alerts
|

Association between Metabolic Syndrome and Hepatitis B Virus Infection in the Roma Population in Eastern Slovakia: a Population-Based Study

Abstract: The prevalence of chronic hepatitis B and simultaneous presence of MS was high among Roma. HBsAg-positive patients had lower levels of total and LDL cholesterol along with decreased apolipoprotein B100. The viral load of chronic hepatitis B patients with MS was higher than in patients without MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Our study group included only adults and as such, the prevalence of HBV infection among our study group was slightly higher than the prevalence for the general population. The relationship between HBV and MetS remains inconclusive [10][11][12][13][14][15][16][17][18] , with some studies reporting a protective effect of HBsAg seropositivity against MetS while other studies found no association between HBsAg positivity and MetS 20 . It is important to note, however, that most studies regarding the association between HBV and MetS have been performed in Taiwan, Japan, Korea, Slovakia and the United States, with few studies having been conducted in China.…”
Section: Discussionmentioning
confidence: 99%
“…Our study group included only adults and as such, the prevalence of HBV infection among our study group was slightly higher than the prevalence for the general population. The relationship between HBV and MetS remains inconclusive [10][11][12][13][14][15][16][17][18] , with some studies reporting a protective effect of HBsAg seropositivity against MetS while other studies found no association between HBsAg positivity and MetS 20 . It is important to note, however, that most studies regarding the association between HBV and MetS have been performed in Taiwan, Japan, Korea, Slovakia and the United States, with few studies having been conducted in China.…”
Section: Discussionmentioning
confidence: 99%
“…Apoliproteins family contains several sub-classes, including ApoA, ApoB, ApoC and so on. Previous study showed that plasma ApoA1, ApoB and ApoA5 levels are decreased in CHB patients [14, 19, 20]. It is indicated that HBV suppresses the synthesis and secretion of ApoA1 by inducing the hypermethylation of the ApoA1 promoter [21], inhibits the expression of ApoB via the suppression of microsomal triglyceride transfer protein [22] and blocks the levels of ApoA5 through its core gene [14].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between CHB and MetS has been explored in ten studies, nine of which focused on Asian populations [4][5][6][7][8][9][10][11][12][13]. The pooled estimates of a recent meta-analysis of 13 observational studies revealed that CHB was associated with reduced risk of MetS in East-Asian populations, in adults under 45 years old, and in males [14].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between CHB and dyslipidemia remained largely ambiguous due to inconsistent associations of CHB and individual lipid biomarker. Seven studies reported significantly lower levels of TC among individuals with CHB as compared to those without CHB [7,9,12,[19][20][21][22]. However, inconsistent findings were reported for TG and HDL-C levels [2,4,5,7,20,23,24].…”
Section: Introductionmentioning
confidence: 99%